2023
DOI: 10.48550/arxiv.2303.05356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hamilton cycles in pseudorandom graphs

Abstract: Finding general conditions which ensure that a graph is Hamiltonian is a central topic in graph theory. An old and well known conjecture in the area states that any d-regular n-vertex graph G whose second largest eigenvalue in absolute value λ(G) is at most d/C, for some universal constant C > 0, has a Hamilton cycle. In this paper, we obtain two main results which make substantial progress towards this problem. Firstly, we settle this conjecture in full when the degree d is at least a small power of n. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As pointed out by Glock, Munhá Correira, and Sudakov [9], it is not even known how to find paths of length longer than n−O( λn d ) in (n, d, λ)-graphs when d/λ ≥ C for some large C. Therefore, looking for general spanning trees in optimal pseudorandom graphs seems to be a quite challenging problem. For almost-spanning trees, however, Alon, Krivelevich, and Sudakov [1] showed that for any ∆ ∈ N and ε > 0, there exists a constant C = C(ε, ∆) such that if G is an (n, d, λ)-graph with d/λ ≥ C, then G contains a copy of each tree with maximum degree bounded by ∆ and at most (1 − ε)n vertices.…”
Section: Question 13 ([1]mentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out by Glock, Munhá Correira, and Sudakov [9], it is not even known how to find paths of length longer than n−O( λn d ) in (n, d, λ)-graphs when d/λ ≥ C for some large C. Therefore, looking for general spanning trees in optimal pseudorandom graphs seems to be a quite challenging problem. For almost-spanning trees, however, Alon, Krivelevich, and Sudakov [1] showed that for any ∆ ∈ N and ε > 0, there exists a constant C = C(ε, ∆) such that if G is an (n, d, λ)-graph with d/λ ≥ C, then G contains a copy of each tree with maximum degree bounded by ∆ and at most (1 − ε)n vertices.…”
Section: Question 13 ([1]mentioning
confidence: 99%
“…The main tool is a powerful embedding technique, sometimes called extendability methods or tree embeddings with rollbacks, which was first introduced by Friedman and Pippenger [7] in 1987 and subsequently improved by Haxell [11] in 2001. Here we will use a modern reformulation of this technique which is attributed to Glebov, Johannsen, and Krivelevich [8], and which has played a major role in the solution of several problems in the last few years (see [3,4,6,9,10,15,13,18,19] for instance). Roughly speaking, the extendability method (Lemma 3.13) says that if we are given a subgraph S i ⊂ G which is 'extendable' and G has good expansion properties, then we can extend S i by adding a leaf e i with one of its endpoints in V (S i ) and other in V (G) \ V (S i ) so that S i + e i remains extendable.…”
Section: Question 14 ([13]mentioning
confidence: 99%
See 1 more Smart Citation